2016
DOI: 10.1140/epja/i2016-16340-6
|View full text |Cite
|
Sign up to set email alerts
|

Collective 2+ 1 excitations in 206Po and 208,210Rn

Abstract: This is an electronic reprint of the original article. This reprint may differ from the original in pagination and typographic detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…These values suggest a constant, or slightly increasing trend with respect to the B(E2; 2 + 1 → 0 + 1 ) value in 204 Pb, instead of the expected more rapid increase, should the seniority regime persist. Based on this observation and QRPA calculations [12], it has been suggested that, at least for the 2 + 1 states of the polonium isotopes, a moderate collectivity sets in immediately when moving away from the closed proton shell [12]. Thus, the energy level pattern and the evolution of the B(E2; 8 + 1 → 6 + 1 ) values suggest that the non-collective seniority regime persists for the N = 122 isotones, as suggested in Refs.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…These values suggest a constant, or slightly increasing trend with respect to the B(E2; 2 + 1 → 0 + 1 ) value in 204 Pb, instead of the expected more rapid increase, should the seniority regime persist. Based on this observation and QRPA calculations [12], it has been suggested that, at least for the 2 + 1 states of the polonium isotopes, a moderate collectivity sets in immediately when moving away from the closed proton shell [12]. Thus, the energy level pattern and the evolution of the B(E2; 8 + 1 → 6 + 1 ) values suggest that the non-collective seniority regime persists for the N = 122 isotones, as suggested in Refs.…”
Section: Introductionsupporting
confidence: 54%
“…Thus, the energy level pattern and the evolution of the B(E2; 8 + 1 → 6 + 1 ) values suggest that the non-collective seniority regime persists for the N = 122 isotones, as suggested in Refs. [5,10], while the newly measured values of the B(E2; 2 + 1 → 0 + 1 ) in 206 Po and 208 Rn indicate a moderate collectivity [12]. This suggests that the transition from single-particle seniority-type mode to collective mode develops differently for low-and high-spin states.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The conservation of seniority imposes a number of simple rules [3,4,6,7] that can be exploited for tracing the evolution from seniority-like behaviour to collectivity with increasing number of valence nucleons [8,9]. Nuclei with two valence nucleons serve as reference points, providing the properties of the basic j 2 configurations such as the energies of states with υ = 2 and the absolute E2 transition strengths for the seniority-changing transition (∆υ = 2) 2 + 1 → 0 + 1 and the seniority-preserving transitions (∆υ = 0) within the υ = 2 multiplet.…”
Section: Introductionmentioning
confidence: 99%